Pendidikan Kesehatan Dengan Media Booklet Meningkatkan Perilaku Personal Hygiene Pada Ibu Nifas - Istiqomah, Henik; Putri, Dinda Destiyani; Satiyem, Satiyem (Jurnal Kebidanan Malakbi, 2023)
One of the reproductive health problems during the puerperium is the lack of knowledge about reproductive health so that it affects unsupportive behavior related to personal hygiene of intimate organs during the puerperium. Personal hygiene in postpartum mothers is very important in order to avoid various reproductive health disorders, especially infections of the female area during the postpartum period. The research design was pre-experimental with a one-group pre-test post-test approach. Collecting data using observation sheets. The sampling technique used was accidental sampling with a sample of 32 postpartum mothers. Techniques of data analysis using the Wilcoxon test. From the results of the study, it was found that all respondents experienced an increase after being given health education through booklets as many as 32 people. The results of the Wilcoxon test analysis obtained p value = 0.000 <0.05. So it can be interpreted that there is a significant influence in providing personal hygiene education for intimate organs with booklet media on improving behavior in postpartum mothers at PMB in the Takeran Magetan Health Center area. So it was concluded that there was an effect of Personal Hygiene Health Education on Intimate Organs with Media Booklets on Behavior Improvement in Postpartum Mothers in PMB in the Takeran Magetan Health Center area.